La chaîne patrimoniale, un régime de visibilité - Véronique Zamant (Territoire en Mouvement)
This paper analyzes a procedure of patrimonialization from the perspective of the dialectic visible/invisible. By doing so, we aim to address the political dimension of cultural heritage and the values at play to produce the city. The analysis of the inscription procedure of a part of the territories of Rio de Janeiro on the Unesco World Heritage list as cultural landscape leads us to consider patrimonialization as an elusive system of visibility, and also as a device reflecting the importance of image in our contemporary society. Our interest in the consequences of this patrimonialization of spaces and practices, invites us to identify socio-spatial situations through other dialectics than the visible/invisible one. These considerations then bring us to question interlinkage between the universalist dimension of patrimonialization and the advent of a generic town. Finally we consider that what is on the margins of the heritage plan invites us to a decentering and illustrates the creative and political power of daily practices and behaviors.